Active smoking and the risk of estrogen receptor‐positive and triple‐negative breast cancer among women ages 20 to 44 years. Issue 7 (10th February 2014) - Kawai, Masaaki; Malone, Kathleen E.; Tang, Mei‐Tzu C.; Li, Christopher I.
<x xml:space="preserve">Abstract</x> BACKGROUND Evidence regarding the correlation between smoking and breast cancer among young women is mixed, and previous studies have not assessed whether smoking is associated differentially with risks of the major breast cancer subtypes. METHODS This was a population‐based, case‐control study of 778 women with estrogen receptor (ER)‐positive breast cancers and 182 women with ER‐negative, progesterone receptor‐negative, and human epidermal growth factor receptor 2‐negative (triple‐negative [TN]), invasive breast cancers ages 20 to 44 years who were diagnosed from 2004 to 2010 in the Seattle‐Puget Sound metropolitan area. A control group of 938 cancer‐free women also was included. Associations between various aspects of smoking history and the risks of ER‐positive and TN breast cancer were assessed using polytomous logistic regression. RESULTS Ever‐smokers had a 1.3‐fold increased risk (95% confidence interval [CI], 1.1‐fold to 1.7‐fold increased risk) of breast cancer overall; and, when stratified by cancer subtype, they had a 1.4‐fold increased risk (95% CI, 1.1‐fold to 1.8‐fold increased risk) of ER‐positive breast cancer, but there was no elevation in their risk of TN disease (odds ratio, 1.1; 95% CI, 0.7‐1.6). Current/recent smokers with a ≥10 pack‐year history of smoking had a 1.6‐fold increased risk (95% CI, 1.1‐fold to 2.4‐fold increased risk) of ER‐positive breast cancer but had no increase in their risk of TN breast cancer (odds ratio, 1.0; 95% CI, 0.5‐1.9). CONCLUSIONS The current results suggested that young women who are current/recent smokers with high pack‐year histories may have an increased risk of ER‐positive breast cancer but not TN breast cancer. Although this association was modest, the findings suggest that an increased risk of ER‐positive breast cancer may be another health risk incurred by young women who smoke. Cancer 2014;120:1026–1034. © 2013 American Cancer Society.